Effective medical leadership in times of emergency: a perspective. Issue 1 (December 2016) - Hershkovich, Oded; Gilad, David; Zimlichman, Eyal; Kreiss, Yitshak
Abstract Leadership, and more specifically medical leadership, is an unmeasured potential that has the power to influence every aspect of a person's professional life and its challenges and is more evident in times of emergency. Medical leadership is receiving increasing recognition especially in discussing actions to be taken in times of stress and emergency. We propose a comprehensive conceptual model that examines the elements that build successful medical leadership, especially during emergency scenarios. The model is based on two sets of medical leadership capabilities and skills, while the first set is more relevant to everyday challenges, the second set represents abilities and characteristics that arise mostly during emergencies. The model gathers together the characteristics and abilities of the medical leader based on our unique personal experiences during conflicts, terror, civilian challenges and numerous humanitarian missions. This article suggests a framework for the foundations on which the medical leader's education should be built and describes our perception of how to establish medical leadership, its unique elements and the processes leading to outstanding performance in times of emergency.